Development Of Integrated-Science Material Using Four Steps Teaching Material Development - Silviana Hendri; Sjaeful Anwar (Journal of Educational Science and Technology (EST), 2019)
The aim of this study are to develop, exam the feasibility, describe the characteristic, and test the student understanding integrated science learning material for Junior High School Student. The theme are developed from volcanic eruption phenomena, which integrated earth science, physics, biology, and social science. The Research and development methode was use to develop integrated science learning material, then captioned “Belajar Sains Melalui Fenomena Erupsi Gunung Api” by Four Steps Teaching Material Development (4STMD). The steps of 4STMD are consist selection, structuring, characterization, and didactical reduction step. Based on the feasibility test, these learning material is qualified in content presetation, language, and graphic feasbility aspects. The characteristic of these learning materials describe that have easy concepts. Based on the understanding test result, the learning material is qualified on good category. It can be conclued that the learning material qualified to be used as supplement learning material of science learning.